A NOTE ON MATRIX APPROXIMATION IN THE THEORY OF MULTIPLICATIVE DIOPHANTINE APPROXIMATION. Issue 3 (28th March 2019) - ZHANG, YUAN
Abstract : We prove the Hausdorff measure version of the matrix form of Gallagher's theorem in the inhomogeneous setting, thereby proving a conjecture posed by Hussain and Simmons ['The Hausdorff measure version of Gallagher's theorem—closing the gap and beyond', J. Number Theory 186 (2018), 211–225].